Impact of previous head and neck cancer on postoperative complications after surgical resection for lung cancer: a case-control study - Briend, Guillaume; Planquette, Benjamin; Badia, Alain; Vial, Amandine; Laccourreye, Ollivier; Pimpec-Barthes, Françoise Le; Meyer, Guy; Sanchez, Olivier (Journal of Thoracic Disease; Vol 10, No 7 (July 31, 2018): Journal of Thoracic Disease, 2018)
Background: Head and neck cancer (HNC) and lung cancer are often linked because of common risk factors. We aimed to assess the risk of postoperative complications in patients with previous HNC undergoing thoracic surgery for lung cancer. Methods: Patients with previous HNC undergoing surgery for lung cancer were included in this retrospective, monocentric, case-control study. All patients were matched for age, sex, FEV1, smoking history, and year of surgery with lung cancer patients without previous HNC. Major postoperative complication was defined as at least one of the following during the first 30 days post lung resection (LR): death, shock, need for mechanical ventilation, and pneumonia. Results: From January 2006 to May 2012, 65 patients with previous HNC underwent LR. Fifty-nine of these patients were included and matched with 120 control patients without HNC. Major complications occurred in 25 [42.4% (95% CI, 29.4–55.4%)] vs. 19 [15.8% (95% CI, 9.2–22.5%)] patients in the HNC and non-HNC groups, respectively (P